Use of trichaderma sp. For Biological Control Of Diplodia Disease In Siam Banjar Citrus - Mujib, Abdul (TROPICAL WETLAND JOURNAL, 2018)
Siam Banjar Citrus has a very bright prospect to be develoved, becomes a contributor to the national fruit products with various types and varieties and has the production that does not depend on seasons. Diplodia disease in citrus still becomes a major problem because it causes loss of high yield and affecth the gain of  production. The disease, caused by Botryodiplodia theobromae pat., indicates symptoms of lesions on citrus trunk, such as narrow lines on the trunk, and can cause plant death due to the disruption of transport of water and nutrients from the soil to the plants. The objectives of the research were to find out the effects of the interaction between Trichokompos fertilizer sp.,to determine the combination of Trichokompos fertilizer and Tricjoderma sp. Solution for Diplodia disease control. The study was conducted from january to april 2012, in Rantau Badauh sub- district. This experiment employed Randomized Blok Design (RBD) consisting of three replications and two factors , namely the dosage of  Trichokompos fertilizer (0 kg, 10 kg and 20 kg), and the dosage of  Trichoderma sp. (0 g/l lt EKG, 50 g/l lt EKG , 100 g/l lt EKG, 150g/l lt EKG and 200 g/l lt EKG). The observations were conducted on the presence of fungi and the measurement of bark lesions. The result showed  that there was no intraction between the two treatmeants, and the significant effect of the application of  Trichoderma sp. Against the widespread symptoms of  doplodia at all observation time with the best dosage was 50 g/l ECG. The results of the regression indicated that the higher concentration and the longer time of the applicatin of Trichoderma sp. Would reduce the widespread of symptoms caused by diplodia in citrus.